The enlargement of painted spiny lobster (Panulirus versicolor) uses different feed ingredients - Anshar, Anshar; Rakhfid, Abdul; Mosriula, Mosriula; Samsibar, Samsibar; Karyawati, Karyawati; Sabara, Ali (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2023)
Development of lobster cultivation activities in Muna regency relatively not optimal.  Availability of feed is be expected to be an obstacle in the development of lobster cultivation.  This Research aims to determine the effect of feed ingredients on growth and survival of spiny lobster (Panulirus versicolor).  The Research was conducted in December 2017 to March 2018, located in Bahari Village, Towea District, Muna Regency, Southeast Sulawesi Province using a randomized block design with three levels of feed ingredients treatment namely treatment A = blood clam meat, treatment B = white shrimp and treatment C = trash fish. The results showed that the highest specific growth rate was obtained in treatment A which was 1.69 ± 0.09 %/day, then treatment C (1.13±0.09 %/day), and the in lowest treatment B (1.09±0,06 %/day). The highest absolute growth was obtained in treatment A of 606.67 ± 15,28 g/individual then treatment C was 336.67±15,28 g/individual and the lowest was in treatment B of 300.00±10.00 g/individual. Survival of sea lobster is 100% in all three treatments. Analysis of variance at the 95% confidence level (α0.05) showed that different feed ingredients had a significantly different effect on the daily growth rate, and the absolute growth of sea lobsters (P. versicolor).